Role of Immunity and Vaginal Microbiome in Clearance and Persistence of Human Papillomavirus Infection - Ntuli, Lungelo; Mtshali, Andile; Mzobe, Gugulethu; Liebenberg, Lenine JP; Ngcapu, Sinaye (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical cancer disproportionately affects women of reproductive age, with 80% of cases occurring in low- and middle-income countries. Persistent infection with high-risk human papillomavirus (HPV) genotypes has been described as the most common non-systemic biological risk factor for the development of cervical cancer. The mucosal immune system plays a significant role in controlling HPV infection by acting as the first line of host defense at the mucosal surface. However, the virus can evade host immunity using various mechanisms, including inhibition of the antiviral immune response necessary for HPV clearance. Pro-inflammatory cytokines and the vaginal microbiome coordinate cell-mediated immune responses and play a pivotal role in modulating immunity. Recently, diverse vaginal microbiome (associated with bacterial vaginosis) and genital inflammation have emerged as potential drivers of high-risk HPV positivity and disease severity in women. The potential role of these risk factors on HPV recurrence and persistence remains unclear. This article reviews the role of vaginal microbiome dysbiosis and cellular or cytokine response in the clearance, persistence, and recurrence of HPV infection.